Recycling of carbon fibre composite material - Lloyd, Rachel Louise (Cranfield University, 2002)
Different routes for recycling carbon fibre composites from the aircraft industry were investigated for feasibility., Literature analysis revealed little previous ·work in this area, with most composite recycling investigations concentrating on automotive industry wastes. The magnitude of disposal of carbon fibre composite materials from the aircraft industry is estimated to be in the region of 350,000 tonnes between the years 2000 and 2050. Landfill cost investigations concluded that the corresponding disposal cost will be in the region of £52 million. Experimentation indicated that the material was stable in landfill conditions, whilst investigations into the health and safety aspects of composite recycling revealed that the materials were harmless unless reduced diameter fibres were released. Activation experiments concluded that the production of commercially viable active carbons was not possible - although the resins activated the carbon fibres did not. Maximum BET surface areas of 170 m2 g- 1 were achieved, despite employing different activation methods and pre-treatments. Therefore, alternative recycling routes were investigated. Two brainstorming sessions generated over forty options. After analysis for of these options were considered most likely to succeed and were investigated in more depth. . Fragment mitigation trials showed a significant reduction in fragment velocity (-20 %) using composite plates of 10.5 mm thickness, liquid-holding boxes resulted in fragment velocity reductions of up to 75 %. Delamination was localised to the area of impact. Literature based investigations of fibre recovery methods identified fluidised bed and high-pressure steam as the most likely to be viable, with fluidised bed plants breaking even at throughputs under 9,000 t/yr. Chemical digestion and resin burn off produced significantly weakened fibres, swelling resulted in the freeing of pre-preg layers. Artificial reef investigations showed that although the material did not appear to degrade in marine environments, it was unsuitable for organism growth. No organisms were attached after a period of 1 year. Pyrolysis appeared to be a viable option, with plants breaking even at throughputs of approximately 6,000 t/yr. Fragment mitigation, fluidised bed fibre recovery and pyrolysis were considered most likely to offer technically and economically viable recycling 1"9utes, and it is recommended that these routes should be investigated further.